STUDENTS’ PERCEPTIONS TOWARD ORAL CORRECTIVE FEEDBACK ON SPEAKING CLASS AT PARAHIKMA INSTITUTE OF INDONESIA - Nurul Istiqamah; Sri Mulyani; Nurfajri Ningsih (International Conference on Social and Islamic Studies, 2021)
This research is aimed to find out students’ perceptions towards oral corrective feedback on speaking class. 2) The types of oral corrective feedback used by the lecturer on a speaking class at Parahikma Institute of Indonesia. This study applied qualitative research design. The total number of participants who had contributed to this research was thirteen. The data were collected by using qualitative questionnaire and in-depth interview and had been analyzed by applying thematic analysis.  The findings showed that there are three main points which were pointed out by the researcher, they are 1) the benefits of oral corrective feedback that includes increasing students’ knowledge, helpful way to improve students’ speaking ability, and giving positive impacts on students’ learning; 2) the drawbacks of oral corrective feedback, were divided into three such as causing nervousness, causing unappreciated feeling, and causing embarrassed and traumatic, 3) students’ expectation of oral corrective feedback includes motivating, encouraging and constructive oral corrective feedback, and appropriate timing in giving oral corrective feedback. In addition, this research also showed the types of corrective feedback usually used by the lecturer in speaking class were recast, elicitation, and explicit correction. The types gave students a clear explanation about their error.